(untitled) (Communications in Computational Physics, 2018)
The Shan-Chen multiphase lattice Boltzmann model (LBM) coupled with Carnahan-Starling real-gas equation of state (C-S EOS) was proposed to simulate three-dimensional (3D) cavitation bubbles. Firstly, phase separation processes were predicted and the inter-phase large density ratio over 2×104 was captured successfully. The liquid-vapor density ratio at lower temperature is larger. Secondly, bubble surface tensions were computed and decreased with temperature increasing. Thirdly, the evolution of creation and condensation of cavitation bubbles were obtained. The effectiveness and reliability of present method were verified by energy barrier theory. The influences of temperature, pressure difference and critical bubble radius on cavitation bubbles were analyzed systematically. Only when the bubble radius is larger than the critical value will the cavitation occur, otherwise, cavitation bubbles will dissipate due to condensation. According to the analyses of radius change against time and the variation ratio of bubble radius, critical radius is larger under lower temperature and smaller pressure difference condition, thus bigger seed bubbles are needed to invoke cavitation. Under higher temperature and larger pressure difference, smaller seed bubbles can invoke cavitation and the expanding velocity of cavitation bubbles are faster. The cavitation bubble evolution including formation, developing and collapse was captured successfully under various pressure conditions.